Designing the Configuration and Selecting the Design Parameters of Drag Systems for Deorbiting Spacecraft Created by Pivdenne Design Office - Alpatov, A.; Lapkhanov, Е.; Palii, O. (Science and Innovation, 2022)
Introduction. To stabilize the space debris environment, defunct spacecraft and mission-related debris shall be deorbited. Problem Statement. The analysis of drag sail systems for deorbiting spacecraft has shown that they are effective for spacecraft deorbiting from orbits having an altitude of up to 800 km, but have some disadvantages: vulnerability of the shell material to space debris fragments that may damage it and electrostatic breakdown. Purpose. The purpose of this research is to design the configuration and to select the design parameters of drag systems for deorbiting spacecraft created by Pivdenne Design Office. Materials and Methods. Methods of space flight mechanics, mathematical modeling of design problems have been used in this research. Results. The calculations have shown that the time of deorbiting Sich-2-1 spacecraft from the design orbit is about 6.5 years for a mass of the drag deorbit system of 9 kg that is 5% of the mass of Sich-2-1 spacecraft. It has been determined that in the case of increasing the deorbit time from the design orbit after the end of operational life to 25 years, the mass of the drag system may be reduced to 4.5 kg. With a mass of the drag deorbit system of 9 kg, the effective use of this DAD system is limited to an altitude from 730 to 750 km, in the case of close to circular orbits of different dislocations, and to an altitude of at most 700 km in perigee and 842 km in apogee in the case of low-elliptical orbits. Conclusions. Based on the requirements of Pivdenne Design Office for the mass and dimensions of the drag augmentation device, the configuration and design view of the drag augmentation device (DAD) have been developed. This design is notable for its compactness that is due to the use of spring mechanisms and low-cost micro-motors, which deploy drag elements. In this design, the device occupies a little space on Sich-2-1 spacecraft.